PENGARUH CITRA MEREK DAN GAYA HIDUP TERHADAP KEPUTUSAN PEMBELIAN PRODUK TAS BRANDED TIRUAN PADA WANITA KARIR DI JAKARTA - Erlita Prasetyaningsih; Diah Fistiani Sukardiman (Universitas Mercu Buana, 2015)
Women aren’t spared from the development of fashion and trends that occur around them. Especially the fashion trends, the producers create products that can attract career women. This is because career women have more ability to buy goods that can improve her class. This research aims to determine the influence of brand image and lifestyle on purchasing decisions imitation branded bags on the career woman in Jakarta. The population in this research is the career woman who likes to use a branded bag. Samples used were as many as 100 people. The sampling technique using is purposive sampling. To answer the problem formulation, purpose and hypothesis of this study, the analysis employed is IBMSPSS Ver. 21.0. Based on the analysis IBMSPSS Ver. 21.0 can be concluded that brand image have positive and significant impact on purchasing decisions. Then lifestyle has positive and significant impact on purchasing decisions.Keyword: Career Woman, Brand Image, Lifestyle, Purchase Decisions